기록관리 분야 국가연구개발사업 현황 분석 - 정회명; 김순희 (Journal of Records Management & Archives Society of Korea, 2023)
The scale of research and development (R&D) investment is increasing to strengthen national competitiveness through technological innovation, leading to an increased interest in investment efficiency. In records management, the National Archives of Korea has been leading the national research and development project since 2008. Accordingly, this study analyzed R&D projects in records management regarding implementing organization, performance or outcomes, and subjects, targeting 111 National Archives of Korea contract research projects from 2008 to 2022. The analysis showed that small and medium-sized enterprises (SMEs) were the most likely to conduct research, the majority of the research outcomes were academic publications, and there were some discrepancies between the reported performance in research and the actual performance. In terms of research subjects, the most common type of records are paper or print documents, establishing an electronic management system among the National Archives' works. In terms of the frequency of keywords in the records management process and research projects, it was found that research was mainly conducted on "preservation." Meanwhile, only 10 cases, or 9% of the 111 projects, were found to be relevant in terms of utilizing big data and developing intelligent technologies related to digital transformation. Therefore, the effectiveness of the R&D project must be improved through follow-up management of the results even after the research project is completed. In addition, in terms of research topics, it was identified that aside from "preservation," studies focusing on "transfer," "classification," "evaluation," and "collection," as well as research that responds to digital transformation, are needed. 기술혁신을 통한 국가경쟁력 강화를 목적으로 연구개발 투자 규모가 증가하고 있으며, 투자 효율성에 대한 관심이 높아지고 있다. 기록관리 분야에서는 국가기록원이 2008년부터 국가연구개발사업을 주도하고 있다. 이에 본 연구는 2008년부터 2022년까지의 국가기록원 용역 연구과제 111건을 대상으로 수행주체, 성과, 주제 등의 측면에서 기록관리 분야 연구개발사업을 분석하였다. 분석 결과, 연구 수행주체는 중소기업, 연구성과는 학술발표가 가장 많았으며, 연구보고서의 성과와 실제 성과 간 일부 차이가 있었다. 연구 주제 측면에서 기록물 형태는 종이문서, 국가기록원 업무 중에서는 전자적 관리체계 구축, 기록관리 업무 과정과 연구과제별 중심단어 빈도 기준으로는 보존에 대한 연구가 주로 수행된 것으로 나타났다. 디지털 전환 관련 빅데이터 활용과 지능형 기술 개발의 측면에서는 111개 과제 중 9%인 10건이 해당하는 것으로 나타났다. 따라서 연구 사업 종료 후에도 성과에 대한 사후 관리를 통해 연구개발사업의 효과성을 높여야 할 것이며, 연구 주제에 있어서는 보존 이외의 이관, 분류, 평가, 생산, 수집 등에 대한 연구와 디지털 전환에 대응하는 연구의 필요성을 확인하였다.